ANALISIS RETURN ON INVESTMENT (ROI) DAN RESIDUAL INCOME (RI) DENGAN DU PONT SYSTEM UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN (Studi pada perusahaan telekomunikasi yang tergabung Indeks LQ 45 di Bursa Efek Indonesia Periode 2008-2012) - Anggraini, Fenda Puspita; ati, Sumi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the financial performance of listed Telecommunication companies in Indonesia Stock Exchange LQ 45 groups in terms of profitability ratios Return On Investment (ROI) and Residual Income ratio (RI) with Du Pont System approac . This type of research is descriptive method with the object of research at PT. XL Axiata Tbk and PT. Telekomunikasi Indonesia Tbk. Data used in this study are secondary data from the 2008-2012 period financial statements. The analysis used is a financial ratio analysis and comparative analysis of the financial statements. The data analysis technique used is the method of Du Pont System Return On Investment (ROI) and Du Pont System Residual Income (RI) by incorporating elements of the calculation of the cost of capital. The analysis showed the company PT. XL Axiata Tbk and PT. Telekomunikasi Indonesia Tbk the period 2008-2012 resulted in the value of the Return On Investment (ROI) is positive while the Residual Income (RI) generates a positive value during the 3 periods. Based on this research can be concluded that the financial performance of PT. Telekomunikasi Indonesia Tbk is better than PT. XL Axiata Tbk in managing the resources of the company and also focuses on the rate of return to investors. Keywords: Financial Performance, Return On Investment ( ROI ), Residual Income ( RI ), Du Pont System.